1999
DOI: 10.1016/s0014-5793(99)00541-4
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits MAPK activity and nuclear translocation in coronary artery smooth muscle: reversal of endothelin‐1 stimulatory effects

Abstract: In porcine coronary arteries, short-term treatment with resveratrol (RSVL) substantially inhibited MAPK activity (IC 50 = 37 W WM); and immunoblot analyses revealed consistent reduction in the phosphorylation of ERK-1/-2, JNK-1 and p38, at active sites. Endothelin-1 (ET-1), a primary antecedent in coronary heart diseases, enhanced MAPK activity, phosphorylation and nuclear translocation in a concentration-responsive but RSVL-sensitive manner. RSVL had no effect on basal or forskolin-stimulated cAMP levels, a k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(63 citation statements)
references
References 45 publications
(64 reference statements)
5
57
1
Order By: Relevance
“…Res was also reported to inhibit the activity of p38 MAPK signaling. For instance, Res inhibited MAPK activity in coronary artery smooth muscle (21). In addition, Res suppressed mouse skin tumor growth by inhibition of activated p38 MAPK (22).…”
Section: Discussionmentioning
confidence: 99%
“…Res was also reported to inhibit the activity of p38 MAPK signaling. For instance, Res inhibited MAPK activity in coronary artery smooth muscle (21). In addition, Res suppressed mouse skin tumor growth by inhibition of activated p38 MAPK (22).…”
Section: Discussionmentioning
confidence: 99%
“…27 In porcine coronary arteries, short-term treatment with resveratrol substantially inhibited mitogen-activated protein kinase activity and reduction in the phosphorylation of ERK1/2. 44 Recently, Haider et al 45 demonstrated that resveratrol inhibits angiotensin IIinduced vascular smooth muscle cell hypertrophy, possibly by interfering mainly with the ERK1/2 signaling pathway. One possible explanation for the inhibitory effect of resveratrol on strain-induced ET-1 gene expression may be its ability to attenuate ROS formation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies suggest that resveratrol modulates all of these pathways. [67][68][69][70] Although contradictory findings exist, the majority of studies agree that the hydroxystilbene activates the ERK1/2 pathways. For example, it has been reported that resveratrol up-regulates ERK1/2 in human neuroblastoma SH-SY5Y cells.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…In addition, resveratrol seems capable of reversing the upregulation of ERK1/2 due to endothelin-1. 69 Nevertheless, although it has not been demonstrated in all the experimental models examined, a good consensus exists that resveratrol activates the RasgMAPK kinaseg MAPK signal transduction pathway. In some specific instance, the activation of this pathway might increase p53 expression and activity (by Ser15 phosphorylation) and, in turn, p53-dependent apoptosis.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%